DEVELOPMENT STRATEGY OF MICRO, SMALL, AND MEDIUM INDUSTRIES BASED ON CREATIVE INDUSTRY CENTERS IN SIDOARJO REGENCY: A CASE STUDY - Putri, Erni Puspanantasari; Aduldaecha, Sukon (Heuristic, 2024)
The variety of creative industries developed by the Sidoarjo people are based on micro, small, and medium-sized industries. It has a positive impact on the people’s economy. These sectors are faced with various problems in developing their businesses, such as marketing, human resources, materials, machinery, capital and finance, products, technology, support, research and development, distribution, promotion, competitors, and policy. The aim of this research is to determine the strategy for developing micro, small, and medium-sized industry-based creative industrial centers in Sidoarjo Regency in an effort to improve the community’s economy. The reasons are that Sidoarjo Regency has a lot of community economic activities on a micro, small, and medium-sized industry scale. Micro, small, and medium-sized industry-based industrial centers that are developing in Sidoarjo Regency include: Ngingas Metal Industrial Center, Jetis Written Batik Industrial Center, Tanggulangin Leather Shoe Craft Industrial Center, Seketi Balongbendo Bamboo Woven Village, Smoked Fish Village in Penatar Sewu, and Cracker Industry Center in Biting Village. Both qualitative and quantitative methods were applied in this research to solve the research problem. The research results indicated that the successful keys of micro, small, and medium-sized industries’s development strategies are as follows: (i) forming village-owned enterprises to support the development of micro, small, and medium-sized industries; (ii) the business motivation is stronger because the businesses are hereditary; (iii) improving business aspects of competitive advantage; (iv) empowering communities to improve their village economies through the development of industrial centers; and (v) the role of governments in developing industrial centers.